(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
This study reports on an improved protocol for callus induction and subsequent regeneration from nodal segment of wood apple (Aegle marmelos L.) Creamish friable competent callus was achieved from nodal segments on MS medium augmented with 4.0 mg1-1 2,4-D within two weeks of inoculation. The callus produced large number of shoots when cultured on MS medium fortified with 2.0 mgl-1 BAP+0.1 mgl-1 NAA within ten days of culture. In vitro raised shoots were rooted on half strength MS medium enriched with 1.0 mgl-1 IBA within fifteen days of culture. The rooted plantlets were successfully established with 80% survival. Key words: Plant regeneration; Callus induction; Nodal explant; Aegle marmelos. DOI: 10.3329/bjsir.v44i4.4590 Bangladesh J. Sci. Ind. Res. 44(4), 415-420, 2009